Sustained Release of Brimonidine from a New Composite Drug Delivery System for Treatment of Glaucoma - Sun, J.; Lei, Y.; Dai, Z.; Liu, Jian; Huang, T.; Wu, J.; Xu, Z.; Sun, X. (American Chemical Society, 2017)
A novel layered double hydroxide (LDH) nanoparticle/thermogel composite drug delivery system (DDS) for sustained release of brimonidine (Bri) has been designed, prepared, and characterized in this study for treatment of severe glaucoma. Brimonidine is first loaded onto LDH (Bri@LDH) nanoparticles, which are then dispersed in the thermogel consisting of plenty of micelles based on poly(dl-lactic acid-co-coglycolic acid)-polyethylene glycol-poly(dl-lactic acid-co-coglycolic acid) (PLGA-PEG-PLGA) copolymer. The Bri@LDH/Thermogel DDS containing 125.0 µg/g of brimonidine has been found to sustainably release the drug for up to 144 h, significantly extending the drug release period compared to that from Bri@LDH nanoparticles. The Bri@LDH/Thermogel DDS is not cytotoxic to human corneal epithelial cells and shows good biocompatibility. In vivo drug release from the special contact lens made of Bri@LDH/Thermogel DDS has been sustained for at least 7 days, which more effectively modulates the relief of intraocular pressure (IOP). Thus, the Bri@LDH/Thermogel DDS is a promising drug delivery alternative that can be used for treatment of severe glaucoma.